Characterization of symptoms and edema distribution in premenstrual syndrome - Tacani PM; Ribeiro DO; Barros Guimarães BE; Machado AFP; Tacani RE (Dove Medical Press, 2015)
Pascale Mutti Tacani,1 Danielle de Oliveira Ribeiro,1 Barbara Evelyn Barros Guimarães,1 Aline Fernanda Perez Machado,2 Rogério Eduardo Tacani1,2 1Physical Therapy Department, São Camilo University Center, 2Physical Therapy Department, São Paulo City University (UNICID), São Paulo, Brazil Background: Premenstrual syndrome is a group of symptoms linked to the menstrual cycle, and edema is among these symptoms. Physiotherapy is often sought by many patients for the treatment of edema; however, for an adequate prescription of physiotherapeutic procedures, the distribution of edema throughout the body has yet to be characterized. Objective: To determine the most frequent symptoms and body regions that present with edema in women during the premenstrual period.Subjects and methods: Sixty women with a mean age of 24.6±4.7 years were evaluated during their premenstrual (between days 21 and 28) and menstrual period (between days 1 and 3), and the collected data included body mass, height, biotype (body-fat distribution), face, breast, limb-circumference measurements, and limb-volume estimate, and an adapted version of the Premenstrual Symptoms Screening Tool was used. Statistical analysis was performed using Student’s t-test and the test for equality of two proportions (P≤0.05).Results: Premenstrual syndrome was identified in 91.7% of the women, and the most frequent symptoms were irritability (73.33%) and physical symptoms, including swelling (65%), and anxiety (58.3%). Edema was detected in the following areas: facial, epigastric, mammary, umbilical, and pubic, the mid-third of the arms, distal forearm, in both thighs and in the mid-third of the legs determined by circumference measurements, and in both upper and lower limbs, according to the estimated volume.Conclusion: In this study population, the most frequent symptoms were irritability, physical symptoms, and anxiety, with distribution of edema in the face, breast, abdomen, pubic area, distal upper limb, and proximal lower limb. Keywords: premenstrual syndrome, menstrual cycle, edema, women’s health, affective symptoms, body surface area